Handbook of Epistemology
XI, 1052 p.
Keywords: Epistemology or theory of knowledge has always been one of the most important -if not the most important -field of philosophy. New arguments are constantly brought to bear on old views, new variants are marshalled to revive ancient stands, new concepts and distinctions increase the sophistication of epistemogical theories. There are a great many excellent textbooks, monographs as well as anthologies consisting of articles in epistemology. Similarly, there are useful philosophical dictionaries which contain a great number of relatively short entries, and general philosophical handbooks which also touch epistemological issues. This volume of 27 essays grew out from the interest to see a handbook which is devoted entirely to the historical roots and systematic development of theory of knowledge. It is not intended to compete but to supplement the already existing literature. It aims at giving both beginners and more advanced students as well as professionals in epistemology and other areas of philosophy an overview of the central problems and solutions of epistemology. The essays are self-contained and stil often rather extensive discussions of the chosen aspects of knowledge. The contributions presuppose very little familiarity with previous literature and only a few of them require the mastery of even elementary logical notation. This, we hope, makes the volume also accessible to the philosophically interested wider audience. The contributors were asked to provide substantial, up-to-date, self-contained and balanced surveys of the various subareas and more specific topics of epistemology, with reference to literature.